2010
DOI: 10.4081/jlimnol.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of bioturbation by the red swamp crayfish Procambarus clarkii to the recruitment of bloom-forming cyanobacteria from sediment

Abstract: The development of cyanobacterial blooms in a small eutrophic pond was monitored along with the potential effect of bioturbation by the red swamp crayfish Procambarus clarkii discussed as well with respect to the recruitment of cyanobacteria from sediment. Cyanobacterial blooms were observed during the early spring and summer. The spring bloom was dominated by Aphanizomenon flos-aquae. Its population density reached the maximum level in late March, thereafter decreasing rapidly and becoming lower than the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 56 publications
0
10
1
1
Order By: Relevance
“…Salinity was the only parameter to differ significantly, which may be influenced by a groundwater seep in NRR at 3900 m 3 . Some studies have suggested P. clarkii may be a source of bioturbation (Mueller 2007, Yamamoto 2010, however, results in this study showed no significant difference in turbidity between the RR and the NRR.…”
Section: Discussioncontrasting
confidence: 81%
“…Salinity was the only parameter to differ significantly, which may be influenced by a groundwater seep in NRR at 3900 m 3 . Some studies have suggested P. clarkii may be a source of bioturbation (Mueller 2007, Yamamoto 2010, however, results in this study showed no significant difference in turbidity between the RR and the NRR.…”
Section: Discussioncontrasting
confidence: 81%
“…In spite of trapping selectivity problems related to size, sex and reproductive stage (e.g. Policar and Kozák, 2005;Gallagher et al, 2006), traps are still the most frequently employed method of capturing crayfish Momot and Gowing, 1972;Byrne et al, 1999;Demers and Reynolds, 2002;Flotemersch and Jackson, 2003;Lyons and Kelly-Quinn, 2003;Martínez et al, 2003;Yamamoto, 2010). Previous studies have shown variable levels of aggression among different crayfish species (Figler et al, 1995(Figler et al, , 1999Gherardi et al, 1999;Gherardi and Daniels, 2004;Tierney et al, 2000;Alonso and Martínez, 2006;Luan, 2009) and in situations of coexistence, traps may underestimate the abundance of the less aggressive species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the burrowing behaviour might also cause river or channel bank erosion and increase water turbidity (Anastácio and Marques, 1997;Rodríguez et al, 2003). These changes in water characteristics alter aquatic ecosystems and are believed to induce cyanobacterial blooms (Yamamoto, 2010).…”
Section: Impactsmentioning
confidence: 99%